The Role of Job Satisfaction as a Mediating Variable Between Work Environment and Employee Productivity - Syahrir, Dian Rahmadhani; Zakaria, Zakaria; Labo, Irwan Adam (Advances in Human Resource Management Research, 2024)
Purpose: This study aims to examine the role of job satisfaction as a mediating variable between the work environment and employee productivity at PT Air Minum Jayapura Robongholo Nanwani. Research Design and Methodology: The research employs a quantitative approach with a sample of 150 employees, utilizing cluster sampling. Data collection was conducted through questionnaires, and the data were analyzed using Structural Equation Modeling (SEM) with AMOS software. Findings and Discussion: The findings indicate that the work environment significantly influences job satisfaction and employee productivity. Moreover, job satisfaction fully mediates the relationship between the work environment and productivity, suggesting that improvements in the work environment led to higher job satisfaction, enhancing productivity. The study's results support theories such as Maslow's hierarchy of needs and Herzberg's two-factor theory. Implications: These findings have practical implications for organizational management, highlighting the importance of creating a conducive work environment to boost job satisfaction and productivity. Future research should consider longitudinal studies and diverse methods to explore these dynamics in different organizational contexts further. This study contributes to human resource management theory by providing empirical evidence of the mediating role of job satisfaction in the relationship between work environment and productivity.